Long‐term administration of the mitochondria‐targeted antioxidant mitoquinone mesylate fails to attenuate age‐related oxidative damage or rescue the loss of muscle mass and function associated with aging of skeletal muscle. Issue 11 (22nd August 2016) - Sakellariou, Giorgos K.; Pearson, Timothy; Lightfoot, Adam P.; Nye, Gareth A.; Wells, Nicola; Giakoumaki, Ifigeneia I.; Griffiths, Richard D.; McArdle, Anne; Jackson, Malcolm J.
ABSTRACT: Age‐related skeletal muscle dysfunction is the underlying cause of morbidity that affects up to half the population aged 80 and over. Considerable evidence indicates that oxidative damage and mitochondrial dysfunction contribute to the sarcopenic phenotype that occurs with aging. To examine this, we administered the mitochondria‐targeted antioxidant mitoquinone mesylate {[10‐(4, 5‐dimethoxy‐2‐methyl‐3, 6‐dioxo‐1, 4‐cyclohexadien‐ 1‐yl)decyl] triphenylphosphonium; 100 μM} to wild‐type C57BL/6 mice for 15 wk (from 24 to 28 mo of age) and investigated the effects on age‐related loss of muscle mass and function, changes in redox homeostasis, and mitochondrial organelle integrity and function. We found that mitoquinone mesylate treatment failed to prevent agedependent loss of skeletal muscle mass associated with myofiber atrophy or alter a variety of in situ and ex vivo muscle function analyses, including maximum isometric tetanic force, decline in force after a tetanic fatiguing protocol, and single‐fiber‐specific force. We also found evidence that long‐term mitoquinone mesylate administration did not reduce mitochondrial reactive oxygen species or induce significant changes in muscle redox homeostasis, as assessed by changes in 4‐hydroxynonenal protein adducts, protein carbonyl content, protein nitration, and DNA damage determined by the content of 8‐hydroxydeoxyguanosine. Mitochondrialmembrane potential, abundance, and respiration assessed in permeabilized myofibers were not significantly altered in response to mitoquinone mesylate treatment. Collectively, these findings demonstrate that long‐term mitochondria‐targeted mitoquinone mesylate administration failed to attenuate age‐related oxidative damage in skeletal muscle of old mice or provide any protective effect in the context of muscle aging.—Sakellariou, G. K., Pearson, T., Lightfoot, A. P., Nye, G. A., Wells, N., Giakoumaki, I. I., Griffiths, R. D., McArdle, A., Jackson, M. J. Long‐term administration of the mitochondria‐targeted antioxidant mitoquinone mesylate fails to attenuate age‐related oxidative damage or rescue the loss of muscle mass and function associated with aging of skeletal muscle. FASEB J. 30, 3771–3785 (2016) www.fasebj.org